Metafísica, mística e linguagem na obra de Schcomo IBN Gabirol (Avicebron): uma abordagem bergsoniana - Macedo, Cecilia Cintra Cavaleiro de (2006)
Schlomo Ibn Gabirol was a Jewish thinker who lived in Spain under Islamic rule. His work was developed in the fields of metaphysics, ethics and poetics. The philosophical text, written in Arabic and translated to Latin as Fons Vitae, was used by the medieval Christian philosophers who, calling him Avicebron, did not known his origin. His poems, written in Hebrew, were incorporated to the Jewish liturgy. In 1847, Salomon Munk discovered that they were the same man. This has made possible the attempt to identify the sources which had influenced the several facets of the author s work, facilitating the contact with the central core of his ideas. The aim of this work is the reconstruction of the author s identity from the comprehension of his work as the reflex of a mystical quest. For such purpose, we use a methodology developed from Henri Bergson indications, who understands the Intuition as a philosophical method, which would be reached through a Mediating Image